Physiological and molecular adaptations during diapause development and overwintering in a heteropteran bug, Pyrrhocoris apterus - Borovanská, Michaela (Jihočeská univerzita, 2009)
In this thesis I present complex experimental data on the physiological and molecular adaptations during diapause development and overwintering in a linden bug, Pyrrhocoris apterus (Heteroptera, Pyrrhocoridae). I focus on adjustments of the enzymatic complement, which is involved in the biosynthesis of cryoprotectants, and heat shock proteins, which are expressed in response to temperature stress.
Physiological and molecular adaptations during diapause development and overwintering in a heteropteran bug, Pyrrhocoris apterus
Keywords: diapause; overwintering; cryoprotectants; heat shock proteins